Characterization of a Broad-Host-Range Lytic Phage SHWT1 Against Multidrug-Resistant Salmonella and Evaluation of Its Therapeutic Efficacy in vitro and in vivo - Tao, Chenglin; Yi, Zhengfei; Zhang, Yaodong; Wang, Yao; Zhu, Hong; Afayibo, Dossêh Jean Apôtre; Li, Tao; Tian, Mingxing; Qi, Jingjing; Ding, Chan; Gao, Song; Wang, Shaohui; et al. (Frontiers in Veterinary Science, 2021)
Inappropriate use of antibiotics has accelerated to the emergence of multidrug-resistant bacteria, becoming a major health threat. Moreover, bacterial biofilms contribute to antibiotic resistance and prolonged infections. Bacteriophage (phage) therapy may provide an alternative strategy for controlling multidrug-resistant bacterial infections. In this study, a broad-host-range phage, SHWT1, with lytic activity against multidrug-resistant Salmonella was isolated, characterized and evaluated for the therapeutic efficacy in vitro and in vivo. Phage SHWT1 exhibited specific lytic activity against the prevalent Salmonella serovars, such as Salmonella Pullorum, Salmonella Gallinarum, Salmonella Enteritidis and Salmonella Typhimurium. Morphological analysis showed that phage SHWT1 was a member of the family Siphoviridae and the order Caudovirales. Phage SHWT1 had a latent period of 5 min and burst size of approximately 150 plaque-forming units (PFUs)/cell. The phage was stable from pH 3-12 and 4-65°C. Phage SHWT1 also showed capacity to lyse Salmonella planktonic cells and inhibit the biofilm formation at optimal multiplicity of infection (MOI) of 0.001, 0.01, 0.1, and 100, respectively. In addition, phage SHWT1 was able to lyse intracellular Salmonella within macrophages. Genome sequencing and phylogenetic analyses revealed that SHWT1 was a lytic phage without toxin genes, virulence genes, antibiotic resistance genes, or significant genomic rearrangements. We found that phage SHWT1 could successfully protect mice against S. Enteritidis and S. Typhimurium infection. Elucidation of the characteristics and genome sequence of phage SHWT1 demonstrates that this phage is a potential therapeutic agent against the salmonellosis caused by multidrug-resistant Salmonella.